Love Your Patient as Yourself: On Reviving the Broken Heart of American Medical Ethics - Tate, Tyler (The Hastings Center report, 2023)
This article presents a radical claim: American medical ethics is broken, and it needs love to be healed. Due to a unique set of cultural and economic pressures, American medical ethics has adopted a mechanistic mode of ethical reasoning epitomized by the doctrine of principlism. This mode of reasoning divorces clinicians from both their patients and themselves. This results in clinicians who can ace ethics questions on multiple-choice tests but who fail either to recognize a patient's humanity or to navigate the ethical quandaries into which they are frequently thrown. Drawing on personal experience as well as the philosophical work of Augustine of Hippo, Simone Weil, and Iris Murdoch, we propose a novel ethical approach grounded in a conception of neighbor love, specifically, the virtue of love understood as attention to a sufferer's humanity. We conclude with five practical recommendations for reimagining medical ethics education oriented around the virtue of love.